Impact of Understanding, Islamic Religiosity, Product Knowledge, and Trust on Intellectual Property Rights Waqf Intentions - Nurul Huda; Nova Rini; Zulihar; Hulmansyah (Jurnal Penelitian, 2023)
This study aims to investigate the Indonesian Muslims' intention toward the intellectual property rights of Waqf. This article uses the quantitative method. This study used 210 respondents who have waqf knowledge. The data analysis method used is the Partial Least Square (PLS) method. The authors' contributions were divided into two. First, the significance of the indicators that make up the variables of intention, Islamic Religiosity, understanding, product knowledge, and trust in waqf institutions regarding the waqf intellectual property rights. Second, the significance of the factors that influence the intention of the Indonesian Muslims in waqf intellectual property rights. It was the Islamic religiosity variable that had a positive and significant influence on the intention of waqf intellectual property rights. The findings of this research support the Indonesian Waqf Board in increasing the collection of waqf assets from Muslim communities in Indonesia. The Indonesian Waqf Board needs to implement various waqf programs to increase the knowledge and understanding of Indonesian Muslims regarding waqf intellectual property rights. The variable Islamic Religiosity needs to increase in Indonesian society since it has a positive and significant influence on the intention of waqf intellectual property rights.